Stability of parameters estimated on Cross-sectional data - Nielsen, Jens Erik; Broegård, Rikke J.; Fosgerau, Mogens (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
This paper discusses the stability of parameters used in models estimated on cross-sectional data and thus the appropriateness of using such models in forecasting. The problem of parameter instability is demonstrated by using a simple logit model for car availability in the Danish households, which is estimated on data from the Danish travel diary data between 1995 and 1999. The combination of using a large and highly reliable data set, together with a simple model makes a good case for examining the inherent stability of the parameters. The effects of wealth on car availability receive special attention because these are expected to change over time. Cohort effects are also addressed.